To the Definition the Deflections of Flexible Non-centrally Compressed Reinforced Concrete Struts Strengthened in the Transverse Direction with Composite Materials - D. R. Mailyan; S. V. Georgiev (Железобетонные конструкции)
An analysis of the calculation methods found in the normative literature on strengthening reinforced concrete structures with composite materials arranged in the transverse direction by the method of wrapping structures showed that there is no calculation method for the second group of limit states.The Code of Rules 164.1325800.2014 does not consider options for strengthening flexible compressed reinforced concrete structures, with the arrangement of composite materials in the transverse direction, introducing restrictions to the dimensions of structures. However, our research suggests the opposite. In this paper, experimental values of deflections of reinforced concrete struts in the transverse direction by composite materials, characteristics and testing methods of prototypes are given. The results of the theoretical calculation of deflections are presented and, based on the comparison of experimental and theoretical values of deflections, an algorithm for calculating the second group of limit states was developed.